THE EFFECT OF THE STEAM APPROACH (SCIENCE, TECHNOLOGI, ENGINEERING, ART, MATHEMATICS) TO INCREASE THEMATIC LEARNING OUTCOMES IN CLASS IV SD NEGERI 007 RAMBAH SAMO - Rahmadani Putri; Sari Nadiatul A’mal; Rejeki Rejeki (Indonesian Journal of Basic Education, 2021)
This study aims to determine that the application of the STEAM approach to improve thematic learning outcomes of fourth grade students of SD Negeri 007 Rambah Samo. The background of this research is that the teacher has difficulty developing learning, the lack of variety of teachers in using the learning approach, this causes student learning outcomes to decline. Meanwhile, to embed a concept requires the application of a certain approach. Based on the results of the researcher's observations, it was found that the results of the test in thematic learning in the Odd Semester of 2021 were that there were still many students who did not achieve minimum completeness (KKM) with a KKM score of 75, the number of students was 25, the percentage of students who completed 30%, and the percentage of students who did not complete 70%. The data analysis technique used is the model of collecting several instruments in the form of student and researcher activity sheets and question sheets. The results of the research can be stated that through the steam approach it can improve learning outcomes of Theme 4 Caring for Living Creatures, Sub Theme I and Sub Theme 2 students of class 1V SD Negeri 007 Rambah Samo. Improved Completeness Learning outcomes in the initial conditions became (34.7%) pre-early, and in cycle 1 (60.9%) and became 85% in cycle 2. The conclusion of this study is that the application of the STEAM approach to improve student learning outcomes in thematic learning Grade IV of SD Negeri 007 Rambah Samo was successful